2008
DOI: 10.1002/hbm.20680
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain imaging of swallowing: An activation likelihood estimation meta‐analysis

Abstract: A quantitative, voxel-wise meta-analysis was performed to investigate the cortical control of water and saliva swallowing. Studies that were included in the meta-analysis (1) examined water swallowing, saliva swallowing, or both, and (2) reported brain activation as coordinates in standard space. Using these criteria, a systematic literature search identified seven studies that examined water swallowing and five studies of saliva swallowing. An activation likelihood estimation (ALE) meta-analysis of these stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
80
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 111 publications
(163 reference statements)
15
80
1
Order By: Relevance
“…ALE is a quantitative method for estimating consistent activation across different imaging studies (Grosbras et al, 2005;Sö rö s et al, 2008;Chan et al, 2009). The ALE analysis was conducted using the standard settings in the Ginger ALE software .…”
Section: Activation Likelihood Estimationmentioning
confidence: 99%
“…ALE is a quantitative method for estimating consistent activation across different imaging studies (Grosbras et al, 2005;Sö rö s et al, 2008;Chan et al, 2009). The ALE analysis was conducted using the standard settings in the Ginger ALE software .…”
Section: Activation Likelihood Estimationmentioning
confidence: 99%
“…Since its introduction, ALE has been applied to many aspects of normal brain function (Decety and Lamm, 2007; Costafreda et al, 2008; Spreng et al, 2009; Soros et al, 2009), as well as in studies of neuropsychiatric and neurological disorders, such as schizophrenia (Ragland et al, 2009; Minzenberg et al, 2009; Glahn et al, 2005), obsessive–compulsive disorder (Menzies et al, 2008), depression (Fitzgerald et al, 2008), and developmental stuttering (Brown et al, 2005). Recently, ALE has been extended to voxel-based morphometry (Schroeter et al, 2007; Glahn et al, 2008; Ellison-Wright et al, 2008) and diffusion tensor imaging studies (Ellison-Wright and Bullmore, 2009).…”
Section: Meta-analytic Approaches To Neural System Modelingmentioning
confidence: 99%
“…Functional brain imaging studies of swallowing in humans has shown a similar pattern of brain activation involving not only the lateral pericentral region similar to the swallowing cortical area in the macaque but also activation in the anterior insula, inferior parietal area and bilateral anterior cingulate (Soros, Inamoto and Martin, 2009). When spontaneous saliva swallowing, volitional saliva swallowing and water swallowing were contrasted using event-related fMRI, a similar pattern of brain activation was found for all three tasks involving the lateral precentral gyrus, lateral postcentral gyrus, and right insula.…”
Section: Swallowing Cns Controlmentioning
confidence: 97%